The effect of trading volume, frequency trade, market capitalization, and sentiment investors on stock returns - Fatmadali Khoirunisa; Siti Nurhayati; M. Sigit Taruna (Business, Accounting, and Knowledge Journal, 2024)
This study aims to examine and analyze trading volume, trading frequency, market capitalization, and investor sentiment toward stock returns. This type of research uses quantitative secondary data obtained from www.idx.co.id. The population in this study is the coal-subsector mining companies listed on the IDX for the 2016–2020 period. The sample for this research is 20 companies. The sampling technique used was purposive sampling. The analysis techniques in this research are descriptive statistics, classical assumption tests, model fit tests, multiple linear regression analyses, and hypothesis testing. The results showed that trading volume had a significant positive effect on stock returns, trading frequency had a significant positive effect on stock returns, market capitalization had a non-significant positive effect on stock returns, and investor sentiment had an insignificant positive effect on stock returns.